2011
DOI: 10.2135/cropsci2010.09.0561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Germplasm Collection of the Cover Crop Hairy Vetch for Use in Sustainable Farming Systems

Abstract: Understanding the association between genotype and agronomically important phenotypes (early flowering, hard seed, and winter hardiness) will facilitate cuitivar selection and inform breeding programs concerned with the cover crop hairy vetch (Vicia vlllosa Roth). We used molecular, observational, and biochemical techniques to identify and evaluate 64 accessions of hairy vetch that originated throughout the world and comprise the USDA National Plant Germplasm System. Time to flowering, percent C, and percent N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
3
38
0
1
Order By: Relevance
“…Caution should be used when evaluating traits posterior to winter survival evaluations, as these traits are confounded if only measured on surviving plants. However, the association of late flowering with winter hardiness has been previously documented in hairy vetch (Jannink et al, 1997; Maul et al, 2011), and this study further illustrates the relationship. These two traits are primary breeding targets to improve the cropping system compatibility of leguminous cover crops in northern regions.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Caution should be used when evaluating traits posterior to winter survival evaluations, as these traits are confounded if only measured on surviving plants. However, the association of late flowering with winter hardiness has been previously documented in hairy vetch (Jannink et al, 1997; Maul et al, 2011), and this study further illustrates the relationship. These two traits are primary breeding targets to improve the cropping system compatibility of leguminous cover crops in northern regions.…”
Section: Discussionsupporting
confidence: 84%
“…last few decades, but they are not well adapted to northern regions of the United States (Maul et al, 2011). Jannink et al (1997) concluded that commercially available hairy vetch in the United States is of two types, subsp.…”
Section: Winter Hardiness and Freezing Tolerance In A Hairy Vetch Colmentioning
confidence: 99%
See 1 more Smart Citation
“…Cover crops terminated 15 June did not exhibit regrowth in treatments where mowing was followed by a termination treatment of roto-till or disk-till. Hairy vetch is only moderately hardy in northern climates [22]. (Table 1).…”
Section: Cover Crop Biomassmentioning
confidence: 99%
“…Seeds, Jersey Shore, PA, USA) and Purple Bounty (Seedway, Hall, NY, USA and United States Department of Agriculture (USDA) Agriculture Research Service, Beltsville, MD, USA). These cultivars were chosen for their commercial availability as well as their differences in maturity as Purple Bounty is an early flowering cultivar and Groff is a later flowering cultivar (Maul et al, 2011).…”
Section: Methodsmentioning
confidence: 99%